Negative feedback regulation of Wnt signaling via N-linked fucosylation in zebrafish - Feng, Lei (Dev Biol, 2014)
L-fucose, a monosaccharide widely distributed in eukaryotes and certain bacteria, is a determinant of many functional glycans that play central roles in numerous biological processes. The molecular mechanism, however, by which fucosylation mediates these processes remains largely elusive. To study how changes in fucosylation impact embryonic development, we up-regulated N-linked fucosylation via over-expression of a key GDP-Fucose transporter, Slc35c1, in zebrafish. We show that Slc35c1 overexpression causes elevated N-linked fucosylation and disrupts embryonic patterning in a transporter activity dependent manner. We demonstrate that patterning defects associated with enhanced N-linked fucosylation are due to diminished canonical Wnt signaling. Chimeric analyses demonstrate that elevated Slc35c1 expression in receiving cells decreases the signaling range of Wnt8a during zebrafish embryogenesis. Moreover, we provide biochemical evidence that this decrease is associated with degradation of Wnt8 ligand and elevated Lrp6 coreceptor, which we show are both substrates for N-linked fucosylation in zebrafish embryos. Strikingly, slc35c1 expression is regulated by canonical Wnt signaling. These results suggest that Wnt limits its own signaling activity in part via up-regulation of a transporter, slc35c1 that promotes terminal fucosylation and thereby limits Wnt activity.